2018
DOI: 10.1002/ana.25295
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of ripple onset predicts outcome in pediatric epilepsy

Abstract: Interictal ripples propagate across iEEG contacts in children with MRE. The association between the onset-ripple-zone resection and good outcome indicates that onset-ripples are promising epilepsy biomarkers, which estimate the epileptogenic tissue better than spread-ripples or onset-spikes. Ann Neurol 2018;84:331-346.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 48 publications
9
93
0
Order By: Relevance
“…These results, taken together with previous findings, suggest that the notion that at least 4–10 cm 2 of synchronously active cortex is necessary to observe epileptiform discharges on the scalp does not hold for ripples . Moreover, icEEG studies showed that ripples are focal events that can appear in individual subdural contacts or be asynchronously present in different contacts . We thus may speculate that ripples on HD‐EEG or MEG reflect multiple focal generators asynchronously activated within a short latency, while focal ripples on individual icEEG contacts (which constitute the majority of icEEG ripples in children with refractory epilepsy) are most likely missed by HD‐EEG or MEG due to spatial undersampling .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These results, taken together with previous findings, suggest that the notion that at least 4–10 cm 2 of synchronously active cortex is necessary to observe epileptiform discharges on the scalp does not hold for ripples . Moreover, icEEG studies showed that ripples are focal events that can appear in individual subdural contacts or be asynchronously present in different contacts . We thus may speculate that ripples on HD‐EEG or MEG reflect multiple focal generators asynchronously activated within a short latency, while focal ripples on individual icEEG contacts (which constitute the majority of icEEG ripples in children with refractory epilepsy) are most likely missed by HD‐EEG or MEG due to spatial undersampling .…”
Section: Discussionsupporting
confidence: 54%
“…To define the icEEG‐ripple‐zone, we analyzed 5–10 min of interictal icEEG data, recorded using XLTEK NeuroWorks (Natus Medical Inc.), as previously described . We detected ripples using a validated automated detector .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that our reproducibility analyses would translate to a host of noninvasive electrophysiology modalities, including scalp EEG and magnetoencephalography (MEG), as the methodology is based generically on event times and locations. Finally, due to nonuniform availability of postresection imaging, we did not attempt to correlate spike propagation patterns with the extent of surgical resection, which has been examined elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…Each coactivation discharge could thus be represented as a spatiotemporal activation sequence , beginning with the earliest spike in the discharge (ie, “leader”) and proceeding through downstream spikes in order of peak latency. For each network, activation sequences were extracted using a previously described algorithm . Briefly, the first detected spike in the network was initialized as the ‘leader’ of a candidate activation sequence, and all subsequent spikes with a latency <50 msec from the leader (or <15 msec from the preceding spike) were appended to the sequence.…”
Section: Methodsmentioning
confidence: 99%